Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5455/medarh.2014.68.159-162
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Glomerular Filtration Rate (eGFR) Values as Predictor of Renal Insufficiency in Advanced Stages of Liver Diseases with Different Etiology

Abstract: Background:Various complications occur in patients with advanced stages of liver diseases. Renal dysfunction, a parameter included in the MELD score, is the most important prognostic factor. There is a strong need in clinical practice to estimate the GFR in this patients.Objectives:The aim of our study was to detect differences in renal function among patients with different stages of chronic liver diseases caused by HBV and HCV, also to determine the impact of viral etiology and gender on the values of eGFR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Our results showed serum CysC and eGFR CysC were superior to SCr and eGFR SCr in the diagnostic performance of kidney impairment in these patients. A recent study also reveals that serum CysC based eGFR may more accurately reflect the GFR in hepatic cirrhosis patients [ 28 ] and thus can be used to evaluate the kidney function [ 29 , 30 ] and prognosis. [ 31 ] In addition, our findings also showed that eGFR CysC had the highest performance in the diagnosis of secondary kidney impairment and its optimal cut-off value was 63.4 mL/min/1.73 m 2 (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed serum CysC and eGFR CysC were superior to SCr and eGFR SCr in the diagnostic performance of kidney impairment in these patients. A recent study also reveals that serum CysC based eGFR may more accurately reflect the GFR in hepatic cirrhosis patients [ 28 ] and thus can be used to evaluate the kidney function [ 29 , 30 ] and prognosis. [ 31 ] In addition, our findings also showed that eGFR CysC had the highest performance in the diagnosis of secondary kidney impairment and its optimal cut-off value was 63.4 mL/min/1.73 m 2 (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Renal dysfunction is one such complication that is characterized by impaired natriuresis, decreased free water clearance, and decreased GFR. [3] In the initial stages of cirrhosis, to maintain effective circulatory volume, cardiac output raises to balance the decrease in systemic vascular resistance. But with disease progression, this compensation becomes ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Optimal management of renal dysfunction in cirrhosis is extremely important as it frequently complicates the clinical course of advanced liver disease and is invariably associated with poor clinical outcomes. [3] Gomes et al . showed in a study that serum creatinine in MELD score had no impact as a prognostic tool for acute kidney injury (AKI) in liver transplant patients, despite its high impact on MELD calculation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiation exposure for both the patient and the operator is significant. Furthermore, the mean age of patients affected by HCC has shifted toward an older age each year and the numbers of HCC patients with coexisting chronic kidney disease, a condition aggravated by chronic liver disease, increase each year. If clinicians can reduce contrast media use by targeting a feeding artery for treatment and at the same time reduce fluoroscopy time, patients will benefit.…”
Section: Discussionmentioning
confidence: 99%